Fostering Learners’ Interpersonal Intelligence through Religious Extracurricular Activities: A Case Study in An Islamic School - Susanti Susanti; Mauhibur Rokhman (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
Research on multiple intelligences has been growing for the last three decades, however, the ones on interpersonal intelligence still need more investigation. This case study explored the development of Islamic school learners’ interpersonal intelligence fostered by religious extracurricular activities. It also sought the factors inhibiting the development of intelligence. The participants of the study were a school principal, vice-principal, extracurricular coach, and three teachers and students at a secondary Islamic school. Data were collected through interviews and observation. The data were then analyzed through data reduction, presentation, and conclusion. The findings revealed that joining religious extracurricular helped learners grow the characters of discipline, self-confidence, empathy or caring, politeness, and togetherness. Meanwhile, factors that inhibit the development of students’ interpersonal intelligence were the influence of surrounding people and gadgets (technology).